Multimorbidity, Trauma Exposure, and Frailty of Older Adults in the Community - Papathanasiou, Ioanna V.; Fradelos, Evangelos C.; Mantzaris, Dimitrios; Rammogianni, Anna; Malli, Foteini; Papagiannis, Dimitrios; Gourgoulianis, Konstantinos I. (Frontiers in Genetics, 2021)
Aim of this study is to investigate the correlation between multimorbidity, traumatic events and frailty among older adults in the community. Studied population consisted of 257 elderly people who were recipients of the services and active members of Open Elderly Care Centers of the Municipality of Grevena and meet a set of selection criteria. The collection of the data was carried out using a fully structured questionnaire, which consisted of two sections: a. form of individual features and b. the Tilburg Frailty Scale-TFI. The sample consisted of 114 men (44.4%) and 143 women (55.6%), aged between 61 to 96 years with an average of 75.12 years. The results showed that the mean scores were for the Physical Frailty 2.70 (std = 2.16), for the Mental Frailty 1.43 (std = 1.21), for the Social Frailty 1.32 (std= 0.64) and for the total Frailty 5.44 (std = 3.02). The majority of the older people had relatively low values of frailty. The Physical, Mental and Total Frailty are related to a. The presence of two or more chronic diseases or disorders, b. The experience of a serious illness in the previous year and c. The experience of a serious illness of a loved one during the previous year. The outcomes helped to identify the frailty syndrome in the elderly, and the factors associated with it.